Production Risk of Rice in Kebonsari, Madiun Regency - Rosita Dewati; Lestari Rahayu Waluyati (Agro Ekonomi, 2018)
ABSTRACTThis study aims to determine the risks, factors affecting risk and investigate the attitude  toward risk in Kebonsari, Madiun regency. This research used primary and secondary data. Primary data obtained purposively by 61 respondents. Coefficient of variation (CV) method was used to analyze the risk, while Just and Pope model was used to analyze the factors affecting production risk. Attitude toward risk was analyzed with Moscardi and de Javnry model. The result of production risk analysis shows that production of rice farming in Kebonsari Madiun regency has a low variation which is about 14,80%. It means that production risk faced by paddy farmers in this area is low. Phonska fertilizer and other fertilizer are risk-increasing variables whereas liquid pesticide is risk decreasing variable. The result of K (s) indicated that 91,60% or 56  paddy farmers are risk averter. About 4,92% of paddy farmers are risk lover and 3,28% are risk neutral. The farmers are behaving in rational manner which avoid the possible risk that might be higher than the revenues to be earned.